Nutrition, Exercise, and Pharmaceutical Therapies for Sarcopenic Obesity - Wakabayashi, Hidetaka; Sakuma, Kunihiro (Journal of Nutritional Therapeutics, 2013)
<!-- [if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> Sarcopenia is characterized by progressive and generalized loss of skeletal muscle mass and strength, with a risk of adverse outcomes such as physical disability, poor quality of life, and death. Sarcopenic obesity is defined as having both sarcopenia and obesity, a condition reported to be associated with a higher risk for adverse outcomes including functional disability, frailty, poor quality of life, longer hospitalization, and higher mortality rates. The definition and diagnostic criteria for sarcopenia have been described by several working groups on the disease; however, there is no standardized definition and diagnostic criteria for sarcopenic obesity. In this review, we summarize nutrition, exercise, and pharmaceutical therapies for counteracting sarcopenic obesity in humans. Although there are some pharmaceutical therapies for both sarcopenia (i.e., testosterone, growth hormone, ghrelin, and vitamin D) and obesity (orlistat, lorcaserin, phentermine-topiramate, and vitamin D), therapies combining nutrition and exercise remain the first-line choice for preventing and treating sarcopenic obesity. Resistance training combined with supplements containing amino acids are considered most effective for treating sarcopenia. Low-calorie, high-protein diets combined with aerobic exercise and resistance training are recommended for preventing and treating obesity. Therefore, nutrition therapies (low-calorie, high-protein diets, protein and amino acid supplementation) and exercise therapies (resistance training and aerobic exercise) would be expected to be the most effective option for preventing and treating sarcopenic obesity. In cases of severe sarcopenic obesity or failure to achieve muscle gain and weight loss through nutrition and exercise therapies, it is necessary to add pharmaceutical therapies to treat the condition. <!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 10]> <![endif]-->